A rare presentation of undiagnosed multiple sclerosis after the COVID-19 vaccine - Ariana R. Tagliaferri; George Horani; Katherine Stephens; Patrick Michael (Greater Baltimore Medical Center, 2021)
Multiple sclerosis (MS) is an auto-immune mediated neurological disorder that affects the central nervous system and leads to myelin sheath destruction. The pathogenesis of MS involves T helper cells causing inflammation and eventual death of the oligodendrocytes. Etiologies for the development of MS include a combination of genetic, environmental, and immune factors. Vaccines have been proposed to increase the immune response and have reportedly activated some autoimmune disorders. Although certain vaccines such as hepatitis B have been associated with MS, studies have refuted these cases. We present a rare case of a 32-year-old patient who presented with symptoms and suggestive of MS a few days after receiving the COVID vaccine. Laboratory and imaging findings confirmed the diagnosis of MS, and she was started on steroids and discharged in a stable condition a few days after.